ALMA observations of molecular complexity in the Large Magellanic Cloud: the N 105 star-forming region - Sewiło, Marta; Cordiner, Martin; Charnley, Steven B.; Oliveira, Joana M.; Garcia-Berrios, Emmanuel; Schilke, Peter; Ward, Jacob L.; Wiseman, Jennifer; Indebetouw, Remy; Tokuda, Kazuki; Loon, Jacco Th van; Sánchez-Monge, Álvaro; et al. (The astrophysical journal, 2022)
The Large Magellanic Cloud (LMC) is the nearest laboratory for detailed studies on the formation and survival of complex organic molecules (COMs), including biologically important ones, in low-metallicity environments—typical of earlier cosmological epochs. We report the results of 1.2 mm continuum and molecular line observations of three fields in the star-forming region N 105 with the Atacama Large Millimeter/submillimeter Array. N 105 lies at the western edge of the LMC bar with ongoing star formation traced by H2O, OH, and CH3OH masers, ultracompact H ii regions, and young stellar objects. Based on the spectral line modeling, we estimated rotational temperatures, column densities, and fractional molecular abundances for 12 1.2 mm continuum sources. We identified sources with a range of chemical makeups, including two bona fide hot cores and four hot core candidates. The CH3OH emission is widespread and associated with all the continuum sources. COMs CH3CN and CH3OCH3 are detected toward two hot cores in N 105 together with smaller molecules typically found in Galactic hot cores (e.g., SO2, SO, and HNCO) with the molecular abundances roughly scaling with metallicity. We report a tentative detection of the astrobiologically relevant formamide molecule (NH2CHO) toward one of the hot cores; if confirmed, this would be the first detection of NH2CHO in an extragalactic subsolar metallicity environment. We suggest that metallicity inhomogeneities resulting from the tidal interactions between the LMC and the Small Magellanic Cloud might have led to the observed large variations in COM abundances in LMC hot cores.
Gesehen am 17.08.2022